Excited‐State Dynamics of Non‐Luminescent and Luminescent π‐Radicals. Issue 5 (30th September 2019) - Teki, Yoshio
Abstract: Recently, the potential use of organic π‐radicals and related spin systems has been expanded to modern technological applications. The unique excited‐state dynamics of organic π‐radicals can be useful to improve the stability of photochemically unstable organic compounds, make the polarization transfer applicable to information technology, and achieve effective up‐conversion of interest for luminescence bioimaging, among others. Furthermore, highly luminescent stable π‐radicals have been recently reported, which are especially interesting for application in organic light‐emitting devices owing to their potential to provide an internal quantum efficiency of 100 %. Thus, the excited‐state nature of stable π‐radicals as well as the control of their excited‐state spin dynamics are emerging topics both in terms of fundamental science and related technological applications. In this minireview, we focus on the excited‐state dynamics of both photostable non(weakly)‐luminescent and luminescent π‐radicals, which are opposites of each other. In particular, we cover the following topics: 1) effective generation of high‐spin photoexcited states and control of the excited‐state dynamics by using non‐luminescent π‐radicals, 2) unique excited‐state dynamics of luminescent π‐radicals and radical excimers, and 3) applications utilizing excited‐state dynamics of π‐radicals. Abstract : Get radical ! This Minireview focuses on the excited‐state dynamics of luminescent and non‐luminescent π‐radicals. The following topics on both sides are covered: 1) effective generation of high‐spin photoexcited states and control of the excited‐state dynamics by using non‐luminescent π‐radicals, 2) unique excited‐state dynamics of luminescent π‐radicals and radical excimers, and 3) applications utilizing excited‐state dynamics of π‐radicals.